2019
DOI: 10.2147/tacg.s198593
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mitochondrial DNA D-loop sequencing reveals obesity variants in an Arab population</p>

Abstract: Background: The association of mitochondrial DNA (mtDNA) variations with obesity has been investigated in diverse populations across the world. However, such obesity-associated mtDNA examinations are rarely conducted in Arab populations. Materials and methods: We re-sequenced mtDNA displacement loop (D-loop) region of 395 Arab individuals of Kuwait. We categorized the individuals based on their BMI scores as obese (n=232; BMI ≥30 kg/m 2 ), overweight (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The changes in mtDNA D-loop and copy numbers may be a heritable risk factor for PCOS in South Indian women [85]. Several mtDNA D-loop variants and haplogroups have reportedly been associated with obesity in different ethnic populations [98]. For example, D-loop variants m.16292C > T and m.16189 T > C are associated with obesity in Germany [99].…”
Section: Pcos and Mitochondrial Genome Abnormalitiesmentioning
confidence: 99%
“…The changes in mtDNA D-loop and copy numbers may be a heritable risk factor for PCOS in South Indian women [85]. Several mtDNA D-loop variants and haplogroups have reportedly been associated with obesity in different ethnic populations [98]. For example, D-loop variants m.16292C > T and m.16189 T > C are associated with obesity in Germany [99].…”
Section: Pcos and Mitochondrial Genome Abnormalitiesmentioning
confidence: 99%
“…A recent study 17 reported a higher frequency of haplogroup H in the control group (BMI < 25 kg/m 2 ) compared with the group with overweight and obesity (BMI > 25 kg/m 2 ) among Arabs living in Kuwait. The frequency of haplogroup H in our Qatar study cohort was slightly higher in the group without obesity; nevertheless, the difference was not significant compared with the group with obesity, which might be due to differences in the admixture of Arab ethnicities in the region.…”
Section: Discussionmentioning
confidence: 92%
“…None of the reported associations involving mitochondrial DNA variants and obesity passes the Bonferroni corrected P-value thresholds. The threshold value for BMI (30 kg/m 2 ) used to define the obesity and no obesity/control groups differs from that used in previous obesity studies using mtDNA [14][15][16][17]29,[34][35][36] . We set a higher threshold for BMI in our study mainly because of the low number of lean BMI individuals in the cohort (the mean BMI value of the cohort was 32.7 ± 6.8 kg/m 2 ) and the desire to balance the sample sizes of the 2 groups; however, the mean BMI value in the group without obesity was borderline (26.5 ± 2.6 kg/m 2 ), and that of the group with obesity was much higher (at 36.5 ± 5.7 kg/ m 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have led to studies that have evaluated whether mitochondrial dysfunction in obesity is due to inherited sequence variations. Several mitochondrial variants and haplogroups have been associated with obesity in different ethnicities ( Yang et al, 2011 ; Grant et al, 2012 ; Nardelli et al, 2013 ; Flaquer et al, 2014 ; Knoll et al, 2014 ; Ebner et al, 2015 ; Veronese et al, 2018 ; Eaaswarkhanth et al, 2019 ). The genotyping data used in these studies were from the mitochondrial control region ( Nardelli et al, 2013 ; Ebner et al, 2015 ; Veronese et al, 2018 ; Eaaswarkhanth et al, 2019 ) and/or extracted from GWASs ( Yang et al, 2011 ; Grant et al, 2012 ; Flaquer et al, 2014 ; Knoll et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%